Star Wars. The battle of Jakku - Segura, Alex, 1980- (Marvel Worldwide, Inc., 2025)
Marvel's STAR WARS storytelling reaches the post-RETURN OF THE JEDI era! In the wake of the battle of Endor, can Princess Leia, Luke Skywalker and the nascent New Republic stave off an unexpected -- and deadly -- new threat? Because a defiant Imperial is about to take center stage -- and go on the offensive! But what is the deadly villain's connection to Darth Vader? Mon Mothma and Leia must make a difficult decision! Luke hunts for a lost Jedi relic but makes a startling discovery! The underworld simmers with intrigue as an unholy alliance is formed! And a ragtag group of New Republic heroes sets out on a mission -- but their return is not guaranteed!